On-current limitation of high-k gate insulator MOSFETs - Chun-Hsing Shih (Elsevier, 2024)
This work explores the limitation of high-k gate insulator on improving the driving currents of MOSFET devices. The use of high-k gate dielectric prevents from the gate tunneling current to have an acceptable equivalent oxide thickness (EOT) in scaled MOSFETs. However, the effectiveness of continued EOT reduction in strengthening gate control is limited strongly by the non-scalability of the quantum effect of inversion layer thickness. Both classical and quantum–mechanical approaches of inversion layer thickness are presented to study the effective gate capacitances and associated on-state drain currents. The enhancements of drain current and gate capacitance generated by high-k gate dielectrics are gradually saturated when a higher permittivity dielectric is applied.